2014
DOI: 10.1016/j.compbiomed.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Recurring patterns of atrial fibrillation in surface ECG predict restoration of sinus rhythm by catheter ablation

Abstract: Recurring patterns from preprocedural 1-minute recordings of ECG TQ intervals were significant predictors of CA 6-month outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…While there have been several applications of frequency domain analysis and morphology RQA techniques in the setting of catheter ablation of AF, to the best of our knowledge, there has been no study to date that has shown changes in EGMs as a result of directed rotor ablation (outside of conventional pulmonary vein isolation). Previous studies have suggested the role of DF, OI, and RQA in the prediction of short‐ and long‐term outcomes in AF ablation. Several other studies have also suggested that both OI and morphology RQA may describe foci of atrial organization critical to the maintenance of AF.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While there have been several applications of frequency domain analysis and morphology RQA techniques in the setting of catheter ablation of AF, to the best of our knowledge, there has been no study to date that has shown changes in EGMs as a result of directed rotor ablation (outside of conventional pulmonary vein isolation). Previous studies have suggested the role of DF, OI, and RQA in the prediction of short‐ and long‐term outcomes in AF ablation. Several other studies have also suggested that both OI and morphology RQA may describe foci of atrial organization critical to the maintenance of AF.…”
Section: Discussionsupporting
confidence: 93%
“…These measures have been associated with organization and termination of AF following antiarrhythmic therapy and step-wise catheter ablation. [8][9][10][11] While frequency domain analysis primarily describes temporal patterns of atrial activation, recurrence quantification analysis (RQA) techniques describe both morphologic [12][13][14][15] and temporal 16,17 stability of AF on the surface electrocardiogram, intracardiac EGMs, and epicardial EGMs. Analyses of intracardiac EGMs suggest that RQA may characterize underlying AF organization 15 while identifying local areas that may be drivers of AF.…”
Section: Introductionmentioning
confidence: 99%
“…10 Finally, Di Marco et al have introduced the study of recurrence patterns of AF from the surface ECG to predict CA outcome both in paroxysmal and persistent AF. 15 Although the study was performed with a follow-up of 6 months, they reported that several recurrent plot indices were significant predictors of CA outcome. Thus, the AA entropy of recurrence predicted ablation outcome with an AUC of 0.81 and 0.72 for paroxysmal and persistent AF, respectively.…”
Section: Previous Studiesmentioning
confidence: 98%
“…In contrast, other works have reported that improved prediction outcomes can be achieved by combining the information provided by multi-lead surface ECG recording systems. 15,16,20,39,40 Hence, multi-lead and multi-variable analyses considering the proposed spectral indices as well as other relevant time features have to be considered in the future to improve the CA outcome prediction both for paroxysmal and persistent AF.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation